Methodological standards in medical reporting. (20th December 2012) - Sporbeck, Birte; Jacobs, Anja; Hartmann, Vanessa; Nast, Alexander
Summary Published research findings are the basis for health care decisions or further medical research. However, reporting of research methods and findings is often incomplete and of insufficient quality. Poor reporting hampers the assessment of reliability and validity of study results. Strengths and weaknesses of the investigation cannot be completely evaluated and subsequently it can mislead decision making in health care or in further clinical research. Transparent reporting can help minimize misinterpretation of publications. Several guidelines were developed to provide advice for reporting research methods and findings. These reporting guidelines facilitate critical appraisal and interpretation of the studies. The guidelines specify in form of checklists a minimum set of items required for clear and transparent reporting. The checklists focus on design, conduct and analysis of studies in particular issues that might introduce bias into the research. The application of these reporting guidelines is required by many international journals. In this CME article we present guidelines for reporting of randomized controlled trials (CONSORT), observational studies (STROBE) and systematic reviews and meta‐analyses (PRISMA, MOOSE).